1996
DOI: 10.1093/jnci/88.3-4.198
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 (IL-1)-Dependent Melanoma Hepatic Metastasis In Vivo; Increased Endothelial Adherence by IL-1-Induced Mannose Receptors and Growth Factor Production In Vitro

Abstract: Given the multiple and complex cytokine cascade induced in vivo and in vitro during LPS-induced systemic inflammation, IL-1 plays a strategic role. Since IL-1Ra is without side effects in humans, studies on intraoperative infusion of IL-1Ra during tumor resection may be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 0 publications
6
88
0
Order By: Relevance
“…37 IL-1 has been implicated as a factor in tumor progression through induction of cancer cell adhesion and invasion, and through the stimulation of host cells to produce angiogenic and growth factors. 1,9,37 In our study, ManR up-regulation occurred in tumor-activated LSECs through an IL-1-dependent mechanism, and blockade of IL-1 effects by use of IL-1Ra abrogated ManR up-regulation induced by C26 colon cancer cells in vivo. IL-1Ra is a naturally occurring inhibitor to IL-1 that has been shown to decrease tumor growth and metastases, and the use of IL-1 inhibitors as a therapeutic approach in the treatment of cancer has been suggested.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…37 IL-1 has been implicated as a factor in tumor progression through induction of cancer cell adhesion and invasion, and through the stimulation of host cells to produce angiogenic and growth factors. 1,9,37 In our study, ManR up-regulation occurred in tumor-activated LSECs through an IL-1-dependent mechanism, and blockade of IL-1 effects by use of IL-1Ra abrogated ManR up-regulation induced by C26 colon cancer cells in vivo. IL-1Ra is a naturally occurring inhibitor to IL-1 that has been shown to decrease tumor growth and metastases, and the use of IL-1 inhibitors as a therapeutic approach in the treatment of cancer has been suggested.…”
Section: Discussionsupporting
confidence: 49%
“…6 Interestingly, this receptor uses a different binding domain to take up blood-borne collagen alpha chains, 7,8 and contributes to the adhesion of cancer cells to LSECs. [9][10][11] Furthermore, ManR is involved in antigen uptake, processing, and presentation to T cells by LSECs, 12 and it has been suggested that this process diminishes local immune response of the liver. 13 However, it is not known how ManR is regulated during the hepatic microvascular infiltration of cancer cells.…”
mentioning
confidence: 99%
“…[D-6-3 H]-glucosamine hydrochloride (specific activity 0.37 used. 15 Cells were cultured in Dulbecco's modified Eagle's medium supplemented with 10% FCS, 100 U/mL penicillin, and 100 mg/mL streptomycin. Cultures were maintained at 37ЊC in a humidified Centrilobular 6 { 2* 6 { 4* atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…They were identified as a desmin-expressing cell populausing a liquid scintillation b-counter. Cell number was also detertion (98% { 8%), in which half of the cells (50% { 6%) mined in parallel experiments using a previously described method, as follows 15 : cells were fixed in 80% (wt/vol) trichloroacetic acid expressed SMA, as quantified by flow cytometry (Fig. 4A).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies in murine tumor models have demonstrated the protumoral role of inflammatory mediators at distinct phases of malignant progression (5)(6)(7)(8). Conversely, inhibition of selected proinflammatory cytokines (e.g., TNF, IL1) or of inflammation-related transcription factors (e.g., NF-B) has resulted in reduced susceptibility to carcinogenesis and slower tumor development in experimental tumor models (7)(8)(9).…”
mentioning
confidence: 99%